2016
DOI: 10.1128/aac.00243-16
|View full text |Cite
|
Sign up to set email alerts
|

Cefazolin versus Nafcillin for Methicillin-Sensitive Staphylococcus aureus Bloodstream Infection in a California Tertiary Medical Center

Abstract: d Recent observational studies have suggested possible reductions in mortality in patients receiving cefazolin versus antistaphylococcal penicillins. We examined 90-day mortality in patients receiving cefazolin compared to nafcillin for methicillin-susceptible Staphylococcus aureus (MSSA) bloodstream infection (BSI). We identified persons with MSSA BSI admitted to San Francisco General Hospital from January 2008 to July 2013 through a hospital-wide infection surveillance system and confirmed 90-day mortality u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…However, concerns regarding the cefazolin inoculum effect leading to treatment failure, especially for deep seated infections, has dampened the enthusiasm for using cefazolin in MSSA bacteraemias. Emerging data now suggest that cefazolin may be equally or actually more effective than ASP in improving mortality for MSSA bacteraemias with fewer adverse effects, although the data are not uniform [6][7][8][9][10][11][12][13][14][15]. Therefore, we decided to identify these comparative trials, pool the data and perform a meta-analysis to assess the efficacy and safety of cefazolin when compared to ASP in the treatment of MSSA bacteraemias.…”
Section: Introductionmentioning
confidence: 99%
“…However, concerns regarding the cefazolin inoculum effect leading to treatment failure, especially for deep seated infections, has dampened the enthusiasm for using cefazolin in MSSA bacteraemias. Emerging data now suggest that cefazolin may be equally or actually more effective than ASP in improving mortality for MSSA bacteraemias with fewer adverse effects, although the data are not uniform [6][7][8][9][10][11][12][13][14][15]. Therefore, we decided to identify these comparative trials, pool the data and perform a meta-analysis to assess the efficacy and safety of cefazolin when compared to ASP in the treatment of MSSA bacteraemias.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of MRSA infections poses several daunting challenges. Current treatment options for MRSA infections are relatively limited, and include antibiotics that are not only costly, but also substantially less effective, and often more toxic when compared to standard antibiotic treatments for MSSA (25-27). This is in large part due to the perceived inability to use traditional β-lactam antibiotics for MRSA infections (6).…”
Section: Discussionmentioning
confidence: 99%
“…There remains a current debate over the most appropriate β-lactam to treat serious MSSA infections, with CFZ or OXA as the primary candidates (25, 39); most recent MSSA bacteremia studies appear to favor CFZ (16, 26, 27). Further, on balancing adverse events vs efficacy metrics, CFZ is generally regarded as a safer option, due to its decreased renal toxicity risk as compared to the antistaphylococcal penicillins (16, 27). However, there remains concern about CFZ efficacy in “high-inoculum” S. aureus infections (e.g., endocarditis) due to the potential for the undetected presence and induction of genes for Types A or C cephalosporinases that hydrolyze CFZ (39, 40).…”
Section: Discussionmentioning
confidence: 99%
“…The overall rates of adverse drug effects were 7.8% in the cefazolin arm and 3.5% in the oxacillin arm ( p = 0.33). Pollett et al [8] reported a retrospective, single-center cohort study of 30 patients receiving nafcillin and 70 patients receiving cefazolin for treatment of MSSA BSI in which mortality rates at 90 days were 16.7% in the nafcillin group and 7.1% in the cefazolin group. The unadjusted odds ratio for 90-day mortality in patients receiving cefazolin was 0.38 (95% confidence interval 0.10–1.44; p = 0.16).…”
Section: Discussionmentioning
confidence: 99%